Penegakan Hukum Hak Cipta Terhadap Download Film Pada Situs Ilegal - Arixellis Juan Efraim Hahury; Theresia Nolda Agnes Narwadan; Muchtar Anshary Hamid Labetubun (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Copyright is the exclusive right of the creator that arises automatically based on declarative principles after a work is realized in a tangible form, without reducing restrictions in accordance with the provisions of laws and regulations. Copyright has been protected by Law Number 28 of 2014. But in reality, there are still many copyright violations such as downloading movies on sites on illegal sites.Purposes of the Research: This study aims to determine Copyright Law Enforcement Against Downloading Films on Illegal Sites. Methods of the Research: The type of research used in this thesis is the type of empirical research. The data collection method used is the method of observation, interviews and literature then the data obtained were analyzed descriptively qualitatively so as to reveal the expected results and conclusions on the problem.Results of the Research: The results of the study show that the enforcement of copyright law on downloading films on illegal sites has not been carried out in accordance with applicable law. This is based on the fact that copyright law enforcement is influenced by several factors, namely legal factors, law enforcement, infrastructure, society and culture. Legal factors, in this case the Law, have contained regulations related to copyright, but law enforcement factors have not been effective in carrying out their duties. In addition, the infrastructure factor in this case is related to the lack of support for communication facilities which is an obstacle related to reporting copyright infringement. Then the community factor and cultural factor, in this case the community still commits violations related to film copyright.